2000
DOI: 10.1007/pl00002344
|View full text |Cite
|
Sign up to set email alerts
|

3D Interstitial HDR Brachytherapy Combined with 3D External Beam Radiotherapy and Androgen Deprivation for Prostate Cancer Preliminary Results

Abstract: The new 3D HDR brachytherapy technique, combined with 3D external irradiation and androgen deprivation, is a feasible, so far well-tolerated and effective treatment in the short-time follow-up of median 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2001
2001
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
(19 reference statements)
1
15
0
1
Order By: Relevance
“…Proctologic complications following conventional external radiation for prostate cancer have been reported to range from 6.6 to 14% (21). Most studies using a combination of HDR brachytherapy and external beam radiation found the incidence of grade 2 or greater proctitis to be less frequent (1.9-11.4%) (15)(16)(17)(18)(19)(20). Treatment plans exposing more than 40% of the anterior rectum to more than 75 Gy with conventional fractionation have been associated with an increase in the incidence of rectal bleeding (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proctologic complications following conventional external radiation for prostate cancer have been reported to range from 6.6 to 14% (21). Most studies using a combination of HDR brachytherapy and external beam radiation found the incidence of grade 2 or greater proctitis to be less frequent (1.9-11.4%) (15)(16)(17)(18)(19)(20). Treatment plans exposing more than 40% of the anterior rectum to more than 75 Gy with conventional fractionation have been associated with an increase in the incidence of rectal bleeding (21).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several investigations of combined treatment using different regimens (15)(16)(17)(18)(19)(20). The total biological effect of the combined treatment is usually difficult to determine.…”
Section: Discussionmentioning
confidence: 99%
“…Other HDR BT (/100 Gy) papers report 2 Á/11% grade 2Á/4 late GI toxicity [9,12,13,19], while papers reporting toxicity after conformal EBRT dose escalation (74 Á/79 Gy) [16,32 Á/34] indicate 6 Á/14% grade 2 Á/4 toxicity and papers concerning conventional/conformal EBRT (64Á/70 Gy) [17,30,35,37] report 5 Á/15%. The definition of the assessment point for late effects varies from 4 months to 24 months or more in these studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…In radiation therapy major improvements have been made by the introduction of 3-D conformal therapy techniques especially for prostate cancer [9,12,20]. Many critical parameters have been examined e.g.…”
Section: Discussionmentioning
confidence: 99%